Potential Use of Papaya Flower Extract (Carica papaya Linn) for Aedes Aegypti Larvicide - Pakan, Sikhry Christian Max; Riwu, Yuliana Radja; Landi, Soleman; Tira, Deviarbi Sakke (Faculty of Public Health, Universitas Diponegoro, Semarang, Indonesia, 2023)
Introduction: Temefos as a larvicide to prevent dengue hemorrhagic fever is known to be resistant to Aedes aegypti larvae in several regions in Indonesia. Therefore, alternative larvicides are needed. Papaya plants are one of the alternative solutions as papaya flowers contain secondary metabolite compounds that can kill Aedes aegypti larvae. This study aimed to determine the potential of papaya flower extract to be an Aedes aegypti larvicide.Methods : This study was a true experimental study with a posttest-only control group design, with 6 treatment groups namely 1%, 5%, 10%, 15%, and 20% extract concentrations (Experimental Group) and distilled water (Control Group). The experiment was repeated 4 times with a testing time of 24 hours. A total 600 Aedes aegypti instar larvae III/IV were used. Larvae toxicity was analyzed using Probit Analysis to determine the value of Lethal Concentration (LC) and Lethal Time (LT) and the Kruskall-Wallis test to determine the differences of larval deaths in each experimental group. Results: Results showed that the highest and the lowest average larval mortality was at 20% concentration (25 larvae) and 1% concentration (14.75 larvae), respectively. and values were 4.84% and 10.39%, while values of five concentrations were 115.74, 24.24, 23.41, 25.24, and 16.55 hours and values of five concentrations were 241.95, 29.42, 26.20, 32.24, and 24.48 hours. There was a difference in the number of larval deaths after 24 hours of treatment in the experimental group (p-value = 0.011).Conclusion: Papaya flower extract has the potential to be an Aedes aegypti larvicide with 20% concentration as the optimum dose. However, phytochemical screening needs to be done to determine the dominant papaya flower compounds act as Aedes aegypti larvicides.